The funding of new technology-based firms in Brazil. (18th July 2006) - Andreassi, Tales; Madureira Rodrigues Siqueira, Eduardo
Around 50% of Brazilian firms shut down before the end of three years. This ratio can be considered to be high, particularly when compared to the ratio for firms in developed countries, which is between 30% and 40%. Certainly, one of the main causes of this mortality rate is the lack of financing. If even established firms have trouble financing their day-to-day activities, it is even more difficult for new businesses, particularly very innovative ones, with new technology-intensive products or processes, as the risk inherent in these businesses is higher. In this sense, the purpose of this article is to discuss the main forms of financing available for innovation and to analyse some financing choices open to Brazilian entrepreneurs interested in starting up a new technology-based business. To this end, we carried out a literature review on the main forms of financing new businesses domestically and abroad, as well as an empirical survey using the participant observation technique, according to which we visited institutions with the purpose of obtaining financial support to establish a technology-based business.